N-Doped graphene as a metal-free catalyst for glucose oxidation to succinic acid. Issue 8 (7th April 2017) - Rizescu, Cristina; Podolean, Iunia; Albero, Josep; Parvulescu, Vasile I.; Coman, Simona M.; Bucur, Cristina; Puche, Marta; Garcia, Hermenegildo
Abstract : N-Containing graphenes have been found to act as catalysts for the selective wet oxidation of glucose to succinic acid. Abstract : N-Containing graphenes obtained either by simultaneous amination and reduction of graphene oxide or by pyrolysis of chitosan under an inert atmosphere have been found to act as catalysts for the selective wet oxidation of glucose to succinic acid. Selectivity values over 60% at complete glucose conversion have been achieved by performing the reaction at 160 °C and 18 atm O2 pressure for 20 h. This activity has been attributed to graphenic-type N atoms on graphene. The active N-containing graphene catalysts were used four times without observing a decrease in conversion and selectivity of the process. A mechanism having tartaric and fumaric acids as key intermediates is proposed.